Simulation of hydrate dissociation equilibrium for carbon dioxide-methane mixture - Huong, V. T. (Array, 2008)
Summary: The objective of the present studyis to explore the potential of removing carbon dioxide from natural gas byforming gas hydrate. The parameters governing the dissociation of gas hydrate have been identified. An attempt has been made to select the favorable operating conditions for methane-carbon dioxide separation through the dissociation of gas hydrate. The K-factor method along with Peng-Robinson equation of state are employed in ICON simulator to obtain hydrate dissociation temperature and pressure, and phase equilibrium compositions